Decomposition of Gender Wage Inequalities through Calibration: Application to the Swiss Structure of Earnings Survey - Guinand, Mihaela Catalina; Tillé, Yves (My University, 2017)
This paper proposes a new approach to decompose the wage difference between men and women that is based on a calibration procedure. This approach generalizes two current decomposition methods that are re-expressed using survey weights. The first one is the Blinder-Oaxaca method and the second one is a reweighting method proposed by DiNardo, Fortin and Lemieux. The new approach provides a weighting system that enables us to estimate such parameters of interest like quantiles. An application to data from the Swiss Structure of Earnings Survey shows the interest of this method.
Keywords: Blinder-Oaxaca; Gender wage discrimination; Quantiles; Reweighting; Wages